Policy‐driven customization of cross‐organizational features in distributed service systems. (13th October 2011) - Walraven, Stefan; Lagaisse, Bert; Truyen, Eddy; Joosen, Wouter
SUMMARY: In a cross‐organizational context, software services are provided and consumed by different organizations. Ensuring that the non‐functional requirements of all the involved organizations are satisfied is hard to achieve in such a distributed and heterogeneous environment: the implementation of features, for example, security, is scattered across the services of multiple organizations. In this paper, we present a coordination architecture for flexible and policy‐driven composition of cross‐organizational features in distributed service systems. The underlying approach of this architecture is to specify the features and their composition at a higher level that abstracts the internal implementation mechanisms of the organizations involved. By means of feature composition policies, the organizations specify at a fine‐grained level which features are required and when they have to apply. Driven by these policies, our coordination middleware dynamically integrates the appropriate features throughout the cross‐organizational service composition in a consistent and efficient way. We have validated our architecture in a proof of concept showing limited performance overhead. Copyright © 2011 John Wiley & Sons, Ltd.